P05.56 Treatment algorithm of patients with primary CNS germinoma: the experience of N.N. Burdenko Neurosurgery Institute - Kobiakov, G L; Poddubskiy, A A; Pitskhelauri, D I; Mazerkina, N A; Ataf’eva, L I; Absalyamova, O V; Trunin, Y Y; Serova, N K; Grigoryeva, N N; Ryzhova, M V; Shishkina, L V; Kalinin, P L; et al. (Neuro-oncology (Charlottesville, Va.), 2018)
Abstract Background To evaluate the efficacy and outcomes of the complex treatment of primary CNS germinoma in patients in non-child population, evaluate the dynamic of the ophthalmological and endocrine functions. Material and Methods The retrospective analysis of 91 patients aged above 16 years with histologically verified primary CNS germinoma was performed. All patients underwent biopsy or surgery with subsequent shunting operation, if indicated. From 2 to 6 cycles (mainly 4 cycles, in 81 cases) of cisplatin and etoposide regimens combination was applied. After chemotherapy all patients underwent either whole ventricular (70 cases) or whole brain (19 cases) or craniospinal irradiation (2 cases) with 24 Gy in 12 fractions. The endocrine status of patients before and after treatment was evaluated in 44 cases. The dynamic of ophthalmological deficit was followed in 31 cases. Endocrine status at different stages of treatment was followed in 74 cases. Results All patients, who underwent combined treatment with chemotherapy and irradiation achieved a complete remission. Median follow-up time was 48 months (1–196 months). 5-year overall survival and progression-free survival rates were 96 and 92 % respectively. 7 patents out of 91 had a relapse within first 5 years of follow-up. The visual disturbances improved in 35%, oculomotor function improved in 5% of patients. Endocrine status improved in 20% of patients with initial deficit. Conclusion Complex treatment of primary CNS germinoma, utilizing 4 cycles of cisplatin + etoposide regimen with subsequent 24 Gy whole ventricular or whole brain irradiation prove to be a good option, alternating craniospinal irradiation alone. Use of this regimen may preserve and improve the endocrine and ophthalmological deficit.